EFFICIENCY OF USING APPLICATIVE GAMES, RELAY RACES AND TRACKS IN TEACHING THE HANDBALL SPECIFIC CURRICULUM FOR 6TH GRADE STUDENTS - Muha Edison Enrico Eduard; Leuciuc Florin (Editura Univeristatii "Stefan cel Mare" din Suceava, 2020)
In this scientific approach, we have assumed that the use of applicative motion games, relay races and tracks in teaching handball for the 6th grade students will lead to faster acquisition of the technical procedures specific to this game. Teaching handball content in the curriculum by using motion games with specific elements, tracks and relay races in the form of a contest, adapted to the objectives and particularities of the group, will facilitate the transfer of knowledge and will lead to a much faster consolidation of the technique of this sporting game with possible effects on the tactical training of students. The purpose of the study was to highlight the effectiveness of games in the process of learning handball specific procedures. Relay races and preparatory games awaken the interest and pleasure of children for physical education and sports, and this attractive way of training leads to a much faster acquisition of handball specific content from the curriculum. In order to demonstrate the effectiveness of the games in teaching handball themes, we have chosen two groups of 6th grade boy students at "Dr. Simeon şi Metzia Hîj" Primary and Middle School of Volovăţ, aged 11-12 years old.